B40's children academic performance based on lifestyle factor in Seremban / Muhammad Umar Rosli, Nurin Nasuha Hussain and Zuhayra Zafirah Mohd Fadzil - Rosli, Muhammad Umar; Hussain, Nurin Nasuha; Mohd Fadzil, Zuhayra Zafirah (2019)
There is reported news about the issue of certain children from low-income background does not perform well in academic achievement has caught the researcher's attention. Furthermore, existing research shows that there is a relationship between socioeconomic and academic achievement but there are also other factors affecting children's academic performance such as lifestyle. The purpose of this study is to determine factor of family lifestyle such as parent involvements, parent investment and eating habits that can be contributed to children's academic performance by using Factor Analysis. Hence, this study was conducted to identify the patterns of lifestyle factors among B40's parents towards their children by using FP-Growth in RapidMiner. In this study, the researcher uses cluster sampling to get samples from a population of Form 1 students in Seremban district. By using data from 310 parents of Form 1 students who took Ujian Penilaian Sekolah Rendah (UPSR) in 2018, the results gained using Factor Analysis and the researcher confirms to extract two factors which are parent commitment and eating habits since the requirement for factor analysis was fulfilled. Furthermore, the findings for the patterns show that parents who were not strict with their children regarding academic performance tend to achieve fair academic performance.